Conservative medical management combined with follow-up multidetector computed tomography of tracheobronchial injury caused by penetrating injuries: A case report. (December 2022) - Takahashi, Tsuyoshi; Kaneko, Tadashi; Hane, Atsuya; Ito, Asami; Kawamoto, Eiji; Suzumura, Misato; Ueda, Koki; Shinoda, Mari; Ito, Atsushi; Imai, Hiroshi
Abstract: Tracheobronchial injury (TBI) associated with penetrating injuries has various clinical symptoms and often requires urgent surgical repair. A tracheal tube and/or placement of a drainage tube combined with multidetector computed tomography (CT) could be used to manage TBI without surgical repair in eligible patients. In this case report, we describe an 86-year-old woman with subcutaneous emphysema and suspected TBI caused by three knife wounds in her neck. After tracheal intubation at a local hospital, she was transferred to our hospital. On admission, she was diagnosed with subcutaneous and mediastinal emphysema due to TBI, as well as bilateral pneumothorax. We adjusted the position of the tracheal tube to a distal location from the TBI, and placed bilateral thoracic drainage tubes by referring to the CT images taken on admission and during the follow-up. The follow-up CT images revealed healing of the TBI. She did not show any worsening of her symptoms and she was successfully extubated on day 10 of her hospital stay. On day 18, she was considered self-reliant and was transferred to her previous hospital. Based on our experience in this case, we believe that ventilation with appropriate sedation, placement of a tracheal tube, and drainage are important conservative therapies for TBI caused by penetrating injuries. CT is also useful for evaluating the status of TBI.